2012
DOI: 10.1016/j.molbiopara.2011.10.006
|View full text |Cite
|
Sign up to set email alerts
|

The molecular epidemiology of parasite infections: Tools and applications

Abstract: Molecular epidemiology, broadly defined, is the application of molecular genetic techniques to the dynamics of disease in a population. In this review, we briefly describe molecular and analytical tools available for molecular epidemiological studies and then provide an overview of how they can be applied to better understand parasitic disease. A range of new molecular tools have been developed in recent years, allowing for the direct examination of parasites from clinical or environmental samples, and providi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 202 publications
(225 reference statements)
0
50
0
Order By: Relevance
“…As such, research on the horse and sheep strains of E. granulosus led to similar studies on Echinococcus of cattle, pig, camel and cervid origin with the description and characterization of several new strains/genotypes (Thompson and McManus, 2002;Thompson, 2008, Table 2). These studies not only confirmed the existence of a number of host-adapted life cycles in different parts of the world but also provided additional data on developmental differences between strains which may impact on control (Lymbery and Thompson, 2012;Thompson, 2001Thompson, , 2008Thompson and Lymbery, 1988;Thompson and McManus, 2002). These informal groupings were retained for many years but with the advent of molecular characterization they were shown to be genetically distinct (Thompson and McManus, 2001).…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 73%
See 4 more Smart Citations
“…As such, research on the horse and sheep strains of E. granulosus led to similar studies on Echinococcus of cattle, pig, camel and cervid origin with the description and characterization of several new strains/genotypes (Thompson and McManus, 2002;Thompson, 2008, Table 2). These studies not only confirmed the existence of a number of host-adapted life cycles in different parts of the world but also provided additional data on developmental differences between strains which may impact on control (Lymbery and Thompson, 2012;Thompson, 2001Thompson, , 2008Thompson and Lymbery, 1988;Thompson and McManus, 2002). These informal groupings were retained for many years but with the advent of molecular characterization they were shown to be genetically distinct (Thompson and McManus, 2001).…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 73%
“…The term strain was introduced during the period of taxonomic uncertainty to refer to intraspecific variants of Echinococcus with defined phenotypic and subsequently genotypic characteristics (Lymbery and Thompson, 2012;Lymbery, 1990, 1996). The term strain has largely been replaced by genotype as this enabled a numerical system to be developed to refer to the different strains (Table 2).…”
Section: Terminology S0015 P0020mentioning
confidence: 99%
See 3 more Smart Citations